CYP3A5 Gene-Guided Tacrolimus Treatment of Living-Donor Egyptian Kidney Transplanted Patients - Mendrinou, Effrosyni; Mashaly, Mohamed Elsayed; Al Okily, Amir Mohamed; Mohamed, Mohamed Elsayed; Refaie, Ayman Fathi; Elsawy, Essam Mahmoud; Saleh, Hazem Hamed; Sheashaa, Hussein; Patrinos, George P. (Frontiers in Pharmacology, 2020)
Background: Tacrolimus is an approved first-line immunosuppressive agent for kidney transplantations. Part of interindividual and interethnic differences in the response of patients to tacrolimus is attributed to polymorphisms at CYP3A5 metabolic enzyme. CYP3A5 gene expression status is associated with tacrolimus dose requirement in renal transplant recipients. Materials & Methods: In this study, we determined the allelic frequency of CYP3A5*3 in 76 renal transplanted patients of Egyptian descent. Secondly, we evaluated the influence of the CYP3A5 gene variant on tacrolimus doses required for these patients. Results: The CYP3A5*3 variant was the most frequent allele detected at 85.53%. Additionally, our results showed that, mean tacrolimus daily requirements for heterozygous patients (CYP3A5*1/*3) were significantly higher compared to homozygous patients (CYP3A5*3/*3) during the first year after kidney transplantation. Conclusion: This is the first study in Egypt contributing to the individualization of tacrolimus dosing in Egyptian patients, informed by the CYP3A5 genotype.